An Assessment of Lifelong Learning Needs and Policy Effectiveness in Mongolia - Tsegmid, Unubold; Ganbaatar, Uugantsetseg (Advances in Social Sciences Research Journal, 2026)
This study examines the need for lifelong learning and evaluates the effectiveness of related policies in This study investigates the growing need for lifelong learning and evaluates the effectiveness of related policies in Mongolia within the context of rapid socio-economic transformation, technological advancement, and changing labor market demands. Drawing on the theoretical perspectives of Gary Becker, Amartya Sen, and Albert Bandura, the study conceptualizes policy effectiveness through four key dimensions: policy clarity, accessibility of learning opportunities, institutional support, and labor market relevance, and examines their influence on lifelong learning outcomes. A mixed-method research design was adopted, combining quantitative survey data collected from 128 university professors in both public and private institutions with qualitative insights derived from policy documents and stakeholder perspectives. The data were analyzed using descriptive statistics and partial least squares structural equation modeling (PLS-SEM) to test the proposed hypotheses and assess the relationships between policy factors and learning outcomes. The measurement model results confirm satisfactory levels of reliability and validity, indicating the robustness of the constructs used in the analysis. The findings reveal that policy clarity is the only factor with a statistically significant positive effect on lifelong learning outcomes, underscoring its critical role in promoting participation, skill development, employability, and social inclusion. In contrast, accessibility, institutional support, and labor market relevance do not demonstrate significant effects, pointing to gaps between policy design and practical implementation. These results suggest that although a formal policy framework for lifelong learning exists in Mongolia, its effectiveness depends largely on the clarity of its communication and the extent to which it is effectively implemented and experienced by stakeholders. This study contributes to both theoretical and practical discourse by offering an integrated framework for evaluating lifelong learning policy effectiveness. It highlights the need to strengthen policy clarity, improve implementation mechanisms, enhance institutional coordination, and ensure closer alignment with labor market demands in order to support inclusive and sustainable lifelong learning development.